Answer:
For x, the equation is
![x=3(y+5)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/yyx1u9mjehfj604fx2iwc6dn1njueyy94m.png)
Explanation:
Given: the equation x over 3-5=y
We have to solve for x,
Consider the given equation the equation x over 3-5=y
Here, over means divide, so,
Mathematically written as ,
![(x)/(3)-5=y](https://img.qammunity.org/2020/formulas/mathematics/middle-school/p6dl9aox02yez7p85u9zbvc0wmtwkey9br.png)
Solving foor x,
adding 5 both sides, we have,
![(x)/(3)-5+5=y+5](https://img.qammunity.org/2020/formulas/mathematics/middle-school/bu20faisy0g1sq06rkar0xy6u5yygjds4i.png)
On solving, we have,
![(x)/(3)=y+5](https://img.qammunity.org/2020/formulas/mathematics/middle-school/nzzmau0k81cvuu2rjt4xscxf8piplw1aff.png)
Now, multiply both side by 3, we have,
![3((x)/(3))=3(y+5)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/9u8h0r70l9rr1lz3udzexblh8akj61c5qt.png)
On simplification, we have,
![x=3(y+5)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/yyx1u9mjehfj604fx2iwc6dn1njueyy94m.png)
Thus, for x, the equation is
![x=3(y+5)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/yyx1u9mjehfj604fx2iwc6dn1njueyy94m.png)